Didactic games as a means for communicative competence development - Buršík, Bořek (Univerzita Pardubice, 2017)
The thesis deals with the use of educational games for the purpose of English language acquisition with the focus on communicative competence development. In the theoretical part of the thesis, educational games are discussed with attention to their functions, types and usage in English language lessons. Then, levels of communication competence in the Common European Framework of Reference for Languages and key competencies in the Framework Educational Programme for Basic Education are presented. In the practical part of the thesis, educational games in English textbooks for language learners are evaluated, in order to determine their contribution to development of communicative competence and key competencies of learners.
Didaktická hra jako prostřed pro rozvoj komunikační kompetence
Keywords: didaktická hra; komunikační kompetence; výuka anglického jazyka; hodnocení učebnic; klíčové kompetence; didactic game; educational game; communicative competence; English language acquisition; evaluation; key competencies